Reformasi Sistem Hukum Kepelabuhan Pada Pengelolaan Digital Maritime Governance: Antara Efisiensi Layanan Dan Kepastian Hukum - Arika Rosanti Widyaningrum; Nur Handayati; Dudik Djaja (CV. Ulil Albab Corp, 2026)
The digital transformation of Indonesia’s port governance has accelerated through the implementation of systems such as Inaportnet, e-manifest, and e-clearance to improve logistics efficiency. However, regulatory reform has not fully kept pace with technological development, creating potential gaps in legal certainty and accountability. This study aims to analyze the weaknesses of Indonesia’s port legal framework in the era of Digital Maritime Governance and to formulate a reconstruction model that balances service efficiency with legal certainty. The research employs a normative legal approach using statute, conceptual, and comparative methods, supported by empirical data on port digitalization performance. The findings reveal that Government Regulation No. 61 of 2009 does not explicitly regulate the legal standing of electronic port documents, liability for digital system failures, interoperability standards, or maritime cybersecurity obligations. Comparative analysis with Singapore demonstrates the importance of integrating digital systems with a clear legal accountability framework. The study concludes that substantive regulatory reform, including the establishment of a digital accountability and maritime cyber liability regime, is essential to ensure that digitalization strengthens legal certainty, administrative accountability, and the global competitiveness of Indonesia’s port system.